COMPARATIVE ANALYSIS OF «SOFT POWER» OF RUSSIA AND THE EU IN THE POST-SOVIET SPACE - Ruslan S. Mukhametov (Сравнительная политика)
The article is devoted to the study of the «soft power» of Russia in the near abroad in comparison with the «normative power» of the European Union. The work consists of two parts. The first section is devoted to the categorical understanding of the concept of «soft power». Much attention is paid to the resources producing «attractiveness». It is shown that there are no universal components of «soft power». The second part of the paper deals with the «soft» component of Russian foreign policy in the post-Soviet space. In academic and expert circles, there is an opinion that Russia's «soft power» is poorly developed (in comparison with European countries). The article shows that this thesis is not correct: Russian foreign policy norms and principles in the eyes of the majority of post-Soviet States look more attractive than the European Union.